Hubungan Pengetahuan dan Sikap Anak Terhadap Perilaku Pemilihan Makanan Jajanan yang Sehat Di SD Muhammadiyah 16 Karangasem Surakarta - Aisyah, Ulfah Nur; , Dr. Mutalazimah, SKM, M.Kes; , Dwi Sarbini, S.ST., M.Kes (2015)
Background : Knowledge of food and health are very important to learn because knowledge about food and health are internal factors which affect the consumption of snack foods. A positive attitude towards child health may not have a direct impact on children's behavior to be positive, but a negative attitude to health can have an impact on behavior. Snack behaviors associated with school children, who need to be investigated is how much the level of knowledge and attitudes of children who support the election of street food. Objective : The objective of this study is to know the correlation of Knowledge and Attitude of Snack Choice with the children behaviour in choosing the health food in 16 Muhammadiyah elementary School in Karangasem Surakarta. Research Method : the research was an observational study using cross-sectional design. Respondents used are students of class V are 55 children in 16 Muhammadiyah Elementary School in Karangasem Surakarta.The data collection method with simple random sampling with a Pearson correlation analysis. Result : The result showed that the level of knowledge of children about the selection of street food that is 100% better. Children's attitudes about the selection of snack foods that support is 58.2%. The child's behavior on the selection of street food that is 56.4% better. Based on the results of analysis show that there is no relation between knowledge and behavior of children regarding the selection of street food (the value ρ = 0.807) and there was no relationship between attitude and behavior of children regarding the selection of street food (the value ρ = 0.537). Conclusion: There is no correlation between knowledge and attitudes of children toward healthy snack food choices. Keywords: knowledge, attitude, behavior, elementary school students, snack. Bibliography: 29 : 1992-2014